Factors That Can Determine The Performance Of Intelligence Members At The Strategic Intelligence Agency TNI - Sony Krisnu Biantoro; Retno Kusumastuti (Green Publisher Indonesia, 2024)
Changes in the global and national political order are influenced by the national interests of each country, which have been sharpened by the war in Ukraine. This broadens the concept of security from military dominance to information and intelligence control, and introduces new forms of threats such as asymmetric, hybrid, cyber and proxy warfare. Indonesia, with its abundant natural resources, plays a strategic role in this dynamic, but faces significant challenges in the shortage of specially qualified intelligence personnel. Of the 48 intelligence members who carry out Counterintelligence operations, only some have advanced education and experience, as well as adequate counterintelligence qualifications. This research uses SWOT and Fishbone analysis to identify the factors that determine the performance of intelligence personnel, as well as finding strategies and root causes that affect the effectiveness of intelligence operations in Indonesia. The aim is to improve the performance and management of strategic intelligence through enhancing the education, experience, and qualifications of intelligence personnel.